Effectiveness of Self-Compassion Training on Dysfunctional Attitudes and Quality of Life in Mine Explosion Amputees - F. Ghazanfari; M. Shafiei (Afarand Scholarly Publishing Institute, 2017)
Aims: Inefficient attitudes and low quality of life correlate with many behavioral disorders and problems.  The aim of the study was to investigate the effects of self-compassion trainings on inefficient attitudes and quality of life in persions with amputations due to the land-mine explosions.   Materials & Methods: In the controlled pretest-posttest experimental study, 40 men with amputations due to the land-mine explosions, who were under the protection of the Martyrs Foundation of Gilan-E-Gharb Township, were studied in 2016. The subjects, selected via simple random sampling method, were randomly divided into two 20-person groups including experimental and control groups. Data was collected by the inefficient attitudes and quality of life questionnaires. Eight 1-hour compassion-training sessions were conducted in experimental group for two months, while control group received no intervention. Data was analyzed using multi-variable covariance analysis test. Findings: At the posttest stage, the pretest scores having been controlled, the mean scores of inefficient attitudes were significantly lower in experimental group compared to control group (p<0.01). In addition, the mean scores of quality of life and its components were significantly higher than control group (p<0.05). Conclusion: The self-compassion trainings improve the inefficient attitudes and quality of life in persons with amputations due to the land-mine explosions.